Malaysia’s scholarly publishing ecosystem: An insider appraisal of established and emerging models - A., Abrizah; Muhamad, Mat Noor; R., Abd-Shukor (University Malaya, 2025)
This article assesses Malaysia’s scholarly publishing ecosystem through an analysis of five models: university-based journals (UBJs), society journals, independent academic-led publishing initiatives, commercial publisher partnerships, and ministry/government-sponsored journals. Drawing on over two decades of experience and the authors’ role in national journal assessment, it examines the structural, ethical, and financial challenges shaping these models, particularly tensions between Diamond and Gold Open Access frameworks. Findings indicate a system at a pivotal point, where commercial sustainability often conflicts with principles of equitable knowledge dissemination. We argue that publishing models should be explicitly included as evaluation criteria in national frameworks i.e. MyCite, aligning with international practices. Recognizing publisher credibility, governance, and financial transparency as core indicators of quality would help address existing legitimacy gaps. The article concludes with policy-oriented recommendations for reinforcing community-controlled publishing, including the establishment of a National Council of Journal Editors. Such initiatives are vital to preserving Malaysia’s scholarly voice, values, and intellectual heritage within a balanced and globally connected knowledge infrastructure.